Knowledge, Attitude and Practices of Dental Practitioners against Hepatitis B in District Faisalabad - Dr.Abid Rashid; Dr. Ume Habiba; Dr. Muhammad Asif; Dr. Naseem Akhtar; Dr. Sultan Ayaz; Dr. Saadia Khatoon (Journal of Aziz Fatimah Medical and Dental College, 2021)
Objective: To assess the knowledge, attitude and practices of dental practitioners against Hepatitis B in district Faisalabad.